2010
DOI: 10.1016/j.neuropsychologia.2009.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Force-field adaptation without proprioception: Can vision be used to model limb dynamics?

Abstract: Because our environment and our body can change from time to time, the efficiency of human motor behavior relies on the updating of the neural processes transforming intentions into actions. Adaptation to the context critically depends on sensory feedback such as vision, touch or hearing. Although proprioception is not commonly listed as one of the main senses, its role is determinant for the coordination of daily gestures like goal-directed arm movements. In particular, previous work suggests that propriocept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 65 publications
10
78
1
Order By: Relevance
“…After the first 5 s of each trial, the delay increased linearly from 0 to 300 ms in 60 s, then decreased linearly back to 0 ms in 60 s and then remained null for the last 5 s. Right after the six DELAY trials, participants performed three NORMAL trials (similar to the first three trials). Despite the fact that any residuals of motor adaptation were potentially washed off (the visual delay being reset to 0 at the end of each DELAY trial), comparisons between POST-test and PRE-test trials were investigated to assess the presence of aftereffects (Held and Freedman 1963;Sarlegna et al 2010;Shadmehr and Wise 2005). For each participant, breaks were given between trials to avoid fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…After the first 5 s of each trial, the delay increased linearly from 0 to 300 ms in 60 s, then decreased linearly back to 0 ms in 60 s and then remained null for the last 5 s. Right after the six DELAY trials, participants performed three NORMAL trials (similar to the first three trials). Despite the fact that any residuals of motor adaptation were potentially washed off (the visual delay being reset to 0 at the end of each DELAY trial), comparisons between POST-test and PRE-test trials were investigated to assess the presence of aftereffects (Held and Freedman 1963;Sarlegna et al 2010;Shadmehr and Wise 2005). For each participant, breaks were given between trials to avoid fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…In this setting, small proprioceptive errors were used during the exposure phase but always in the presence of kinesthetic information. Another important finding is presented by Sarlegna et al in [44]. They examined the motor behavior of a deafferented patient, deprived of proprioception below the nose, to assess adaptation to new dynamic conditions in the absence of limb proprioception.…”
Section: Contribution Of Visual Feedbackmentioning
confidence: 99%
“…This seems appropriate since learned dynamics have been shown to be strongly represented in intrinsic-frame, joint coordinates (Shadmehr and Mussa-Ivaldi 1994). Interestingly, studies of deafferented patients suffering from several impaired or unreliable proprioception have found that visual information could be used both to improve the feedforward control and accuracy of unperturbed reaching movements (Ghez et al 1995) and, recently, to adapt to a haptic environment (Sarlegna et al 2010). Although deafferented subjects still strongly differ from observers in that they have access to self-generated motor plans, descending motor commands, and other movement-related signals among other aspects, the above studies suggest that visual signals can at least partially compensate for the absence of proprioception in motor control and learning.…”
Section: Observation Of Perturbed Reaches Induced Adaptive Changes Inmentioning
confidence: 99%